Non-Genetic Risk Factors for Dementia and Alzheimer’s Disease - Bazzari, Firas; Bazzari, Amjad (Jordan Medical Journal, 2023)
Alzheimer’s disease (AD) is a multifactorial neurodegenerative disorder linked to multiple genetic and environmental factors. Despite its complex pathology and still undetermined etiology, a number of factors have been found to be closely associated with the incidence of AD. Although the molecular mechanisms linking many of these factors with AD are unclear and not necessarily causative, their identification and control might be key preventative measures. Cardiovascular diseases, diabetes, obesity and other life-style habits are recognized as established risk factors for AD. Other emerging factors investigated as potential contributors to the overall risk of dementia include anemia, obstructive respiratory diseases, vitamin D deficiency, thyroid imbalance, inflammation and depression. This review summarizes established risk factors; it also provides an insight into emerging factors as modifiable elements, the control of which may reduce the risk of AD and dementia.